The Variation and Correlation of Serum Adiponectin, Nesfatin-1, IL-6, and TNF-α Levels in Prediabetes - Huang, Kangkang; Liang, Yunlai; Ma, Yating; Wu, Jiahui; Luo, Huidan; Yi, Bin (Frontiers in Endocrinology, 2022)
Background: The variation and correlation among adiponectin, nesfatin-1, TNF-α and IL-6, which involve in the process from healthy to prediabetes and diabetes have not been elucidated. This study aims to investigate the roles of them in this process. Methods: 72 T2DM, 75 prediabetes and 72 healthy individuals were enrolled and serum adiponectin, nesfatin-1, TNF-α and IL-6 were tested with appropriate kit, and primary data were analyzed with correct method. Results: serum levels of each factor in prediabetes were between T2DM and healthy, and significant differences were found among them. TNF-α and nesfatin-1 levels in T2DM obviously different compared to prediabetes or healthy; IL-6 and adiponectin levels in the healthy group were significantly changed in contrast to prediabetes or T2DM. Correlation analysis found that in prediabetes, adiponectin was positively correlated with TNF-α (R=0.2939, P=0.0105) and IL-6 (R=0.3918, P=0.0005), and the relationship greatly strengthened when prediabetes accompanied by insulin resistant (TNF-α: R=0.7732, P<0.0001, IL-6: R=0.6663, P=0.0005). We also demonstrated that declined adiponectin (OR=6.238, P=0.019), nesfatin-1 (OR=2.812, P=0.01) and elevated TNF-α (OR=5.541, P=0.001) were risk factors for prediabetes towards diabetes. Conclusions: this research proved significant variations of adiponectin, nesfatin-1, IL-6 and TNF-α levels in the healthy, prediabetes and T2DM, suggesting a slow and gradual change during the progression of healthy condition toward diabetes via prediabetes.